Bovine hydroxyapatite for biomedical applications: A review of the effects of crosslinker and Secretome - Abidharma, I Putu Surya; Mahyudin, Ferdiansyah; Edward, Mouli (Edelweiss Applied Science and Technology, 2025)
Bovine Hydroxyapatite (BHA), a naturally derived material with a composition similar to human bone, has emerged as a promising candidate for biomedical applications, particularly in bone tissue engineering and regeneration. This review systematically explores the role of crosslinkers and secretomes in enhancing the properties of BHA scaffolds. Crosslinkers, such as glutaraldehyde, improve the mechanical stability and structural integrity of BHA, while secretomes from Mesenchymal Stem Cells (MSCs) contribute to cellular differentiation, angiogenesis, and tissue regeneration. In vitro and in vivo studies were analyzed to assess the osteoconductivity, biocompatibility, and regenerative potential of BHA scaffolds, particularly in combination with crosslinkers and MSC-derived secretomes. Findings suggest that crosslinkers significantly enhance the mechanical performance of BHA, although their concentration must be carefully optimized to prevent cytotoxicity. Secretomes, on the other hand, amplify the biological activity of BHA scaffolds by promoting angiogenesis and immune modulation, which are essential for tissue integration and healing. The synergistic application of crosslinkers and secretomes offers a promising strategy to optimize BHA scaffolds for bone regeneration. This review highlights the current advancements in the field and identifies future research directions to further refine these approaches for clinical applications in bone and dental tissue engineering.